Sabal lougheediana (Arecaceae), a critically endangered, endemic palm species from Bonaire - Griffith, M. Patrick; Coolen, Quirijn; Barros, Michelle; Noblick, Larry R. (Phytotaxa, 2019)
A new palm species, Sabal lougheediana, is described and illustrated. This critically endangered island endemic, native solely to Bonaire, is characterized by a compact crown of leaves, erect leaf segments, distinctive leaf scars, and frequently vascularized fiber bundles in leaflet transection. Detail on history, morphology, range, habitat, and conservation status is presented, along with a diagnostic key.